3(x - 18) = 5(x -12)
The first thing you need to do is expand both sides. Keep in mind that expanding involves distribution of the number outside of the brackets to each term inside the brackets.
For instance, on the left hand side, I would multiply the 3 with the x, and then the 3 with the 18. Same with the right hand side. Remember to preserve the sign; in this case, since we're subtracting, we'd be subtracting after expanding, too.
3(x) - 3(18) = 5(x) - 5(12)
Now, solve each term.
3x - 54 = 5x - 60
Bring ALL terms with x in them on the left hand side, and everything else to the right hand side.
Whenever you bring a term from one side to the other, it changes from positive to negative, or vice versa. For instance, moving that -54 to the right hand side would make it +54, and moving that 5x to the left hand side would make it -5x.
3x - 5x = -60 + 54
Now, we group like terms, and combine the numbers on the right hand side as well. This gives us
-2x = -6
Now, we divide both sides by -2 in order to isolate the x.
(-2x)/(-2) = (-6)/(-2)
x = 3
2006-12-20 06:53:26
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
X=3
2006-12-20 06:48:52
·
answer #2
·
answered by raindog312 3
·
0⤊
0⤋
x=3
2006-12-20 12:09:55
·
answer #3
·
answered by benjean 1
·
0⤊
0⤋
x=3
2006-12-20 06:50:37
·
answer #4
·
answered by Barry_1362 1
·
0⤊
0⤋
3(x-18)=5(x-12)
first, distribute the 3 to the () on the left side
3x-54=5(x-12)
second, distribute the 5 to the () on the right
3x-54=5x-60
combine like terms
subtract 3x from both sides
-54=2x-60
add 60 to both sides
6=2x
divide
3=x or x=3
2006-12-20 09:32:17
·
answer #5
·
answered by wheels 2
·
0⤊
0⤋
3(x - 18) = 5(x - 12)
3x - 54 = 5x - 60 (Subtract 3x and add 60 to both sides)
2x = 6 (Divide both sides by 2)
x = 3
Check:
3((3) - 18) = 5((3) - 12)
3(-15) = 5(-9)
-45 = -45
QED
2006-12-20 07:25:07
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
that is a undemanding inequality, which skill we could continuously be left with x and yet another value. answer: 5/3 - a million/4x > -2/3x + a million/6 (Transpose a million/6 and -a million/4x) 5/3 - a million/6 > -2/3x + a million/4x (Convert fractions to similar) 10/6 - a million/6 > -8/12x + 3/12x 9/6 > -5/12x (Divide each and every part by technique of -5/12) 9/6(12/-5) > x -3.6 > x (turn the inequality signal because we divided with a detrimental) -3.6 < x or x > -3.6 (answer) desire this helps!
2016-11-27 23:20:10
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
3(x-18)=5(x-12)
3x- 3(18)=5x-5(12)
-3(18)+5(12)=5x-3x
-3(18)+5(12)=2x
(-3)(9) +(5)(4)=x
-27+20=x
3=x.
x=3.
2006-12-20 07:12:33
·
answer #8
·
answered by Rex 1
·
0⤊
0⤋
Distribute, collect like terms, and simplify:
3x - 54 = 5x - 60
2x = 6
x = 3
2006-12-20 06:49:25
·
answer #9
·
answered by computerguy103 6
·
0⤊
0⤋
multiply through so
3x-54=5x-60
then subtract from each side to isolate x's on one side and #'s on the other so
2x= 6
divide out from the x so
x=3
2006-12-20 06:50:05
·
answer #10
·
answered by kgenesius 3
·
0⤊
0⤋